Influence of speech-language therapy on P300 outcome in patients with language disorders: a meta-analysis - Silva, Deise Renata Oliveira da; Menezes, Pedro de Lemos; Almeida, Grazielle de Farias; Souza, Thais Nobre Uchoa; Costa, Ranilde Cristiane Cavalcante; Frizzo, Ana Claudia Figueiredo [UNESP]; Carnaúba, Aline Tenório Lins (Elsevier, 2019)
Introduction: The patient's evolution in the audiology and speech-language clinic acts as a motivator of the therapeutic process, contributing to patient adherence to the treatment and allowing the therapist to review and/or maintain their clinical therapeutic conducts. Electrophysiological measures, such as the P300 evoked potential, help in the evaluation, understanding and monitoring of human communication disorders, thus facilitating the prognosis definition in each case. Objective: To determine whether the audiology and speech-language therapy influences the variation of P300 latency and amplitude in patients with speech disorders undergoing speech therapy. Methods: This is a systematic review with meta-analysis, in which the following databases were searched: Pubmed, ScienceDirect, SCOPUS, Web of Science, SciELO and LILACS, in addition to the gray literature bases: OpenGrey.eu and DissOnline. The inclusion criteria were randomized or non-randomized clinical trials, without language or date restriction, which evaluated children with language disorders undergoing speech therapy, monitored by P300, compared to children without intervention. Results: The mean difference between the latencies in the group submitted to therapy and the control group was −20.12 ms with a 95% confidence interval of −43.98 to 3.74 ms (p = 0.08, I2 = 25% and p value = 0.26). The mean difference between the amplitudes of the group submitted to therapy and the control group was 0.73 uV with a 95% confidence interval of −1.77 to 3.23 uV (p = 0.57, I2 = 0% and p value = 0.47). Conclusion: The present meta-analysis demonstrates that speech therapy does not influence the latency and amplitude results of the P300 evoked potential in children undergoing speech therapy intervention.
Influência da terapia fonoaudiológica no resultado do P300 em pacientes distúrbio de linguagem: uma metanálise
Keywords: P300 evoked potential; Rehabilitation of speech and language disorders; Speech-Language therapy